Savings for resilience: Investigating saving instruments in Mali - Annkathrin Wahbi; Eike Nordmeyer; Tim Ölkers; Oliver Musshoff (PLoS ONE, 2025)
Despite worldwide initiatives to alleviate poverty, 35% of Sub-Saharan Africa’s population continues to live below the poverty line. In light of this, many regard the promotion of saving as a cost-efficient and low-risk strategy for household resilience and pro-poor development. We assess saving determinants for 374 Malian farmers by employing a two-step selection model. As a first step, we assess determinants of whether or not a farmer saves by applying a probit model. In a second step, we estimate an Ordinary Least Squares regression to investigate a farmer’s savings amount. In both steps, we disaggregate the outcome variable on whether respondents save through mobile money, via a bank account, or a secret place. To address endogeneity concerns, we apply an instrumental variable approach using the walking distance to the next mobile money agent as an instrument. We find considerable heterogeneity in saving determinants and identify a particularly strong role of supply-side factors such as infrastructure quality. Furthermore, the results suggest that saving with a secret place is persistently popular, in particular among younger respondents and those who do not have access to a smartphone in their household. This indicates a potential to transfer these hidden savings to formal accounts for interest earnings and potentially safer storage. The findings have implications for improving financial practices and resilience among smallholder farmers in low-income economies, suggesting the transformative potential of secure and accessible saving mechanisms.